2005
DOI: 10.1016/j.cardiores.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of furin-like proprotein convertases in the arterial response to injury

Abstract: This study demonstrates that furin-like PCs are involved in the arterial response to injury possibly through activation of the TGF-beta-Smad signaling pathway and identifies furin-like PCs as a possible target to inhibit intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Sluijter et al [28] demonstrated in a recent study that furin-like protein convertases, proteolytic activators of proproteins, are involved in the vessel response to injury, possibly through activation of the TGF-β-Smad signaling pathway, and identified these activators as possible targets to inhibit intimal hyperplasia. Other studies also centered on protein convertases have indicated that these enzymes play an essential role in vascular diseases owing to their involvement in vascular injury via effects on growth factors and mediators [29].…”
Section: Discussionmentioning
confidence: 99%
“…Sluijter et al [28] demonstrated in a recent study that furin-like protein convertases, proteolytic activators of proproteins, are involved in the vessel response to injury, possibly through activation of the TGF-β-Smad signaling pathway, and identified these activators as possible targets to inhibit intimal hyperplasia. Other studies also centered on protein convertases have indicated that these enzymes play an essential role in vascular diseases owing to their involvement in vascular injury via effects on growth factors and mediators [29].…”
Section: Discussionmentioning
confidence: 99%
“…In adventitial and intimal areas of arteries, the levels of phosphorylated Smad 1/5 and 2/3, MT1-MMP, MMP-2 and furin are increased after balloon dilation. Moreover, furin inhibition can reduce the intimal and adventitial areas, suggesting that furin is involved in neointima formation [84]. The TGF-b-Alk5-Smad2/3 or TGF-b-Alk1-Smad1/5 pathway, which is activated by balloon dilation stimulus, can stimulate collagen production, cell proliferation and migration, and MMP production [85].…”
Section: Furin Promotes Cell Proliferation and Ecm Synthesis By Activmentioning
confidence: 99%
“…In the vessel wall, inactive TGF-␤ can be activated via the cooperation between the mannose-6-phosphate/insulin-like growth factor II receptor and the urokinase-type plasminogen activator receptor, plasmin, thrombospondin, and furin-like proprotein convertases; the latter are responsible for TGF-␤ activation after arterial injury. 1 In contrast, BMPs are secreted in an active form and regulated through reversible interactions with extracellular antagonists, including noggin, chordin, and DAN. 2 These interactions determine the bioavailability of different TGF-␤s/BMPs for binding to their receptors.…”
Section: Tgf-␤ Superfamily Members and Effects On Vascular Cellsmentioning
confidence: 99%